Exo Explorer: A procedurally generated solar system - An application for interactive exploration of a procedurally generated solar system containing diverse ecosystems - Båtsman Hilmersson, Joel; Forsberg, Elin; Gustafsson, Isak; Hansson, Isak; Hästmark, Manfred; Persson, Daniel (My University, 2023)
This project aims to develop a solar system in the Unity game engine, focusing on procedural content generation (PCG) for planets and their ecosystems. PCG, which utilizes algorithms and randomness to generate content automatically, offers a promising approach to create a vast and immersive solar system. This report will present an application of PCG to generate a solar system for users to explore and interact with. Challenges faced during development, such as adapting common 2D programming techniques to 3D spheres, are also discussed. The resulting system includes forests, lakes and various creatures on each planet, with climates adding to the environment’s complexity. The creatures have hunger, thirst, and reproduction capabilities, which contribute to a dynamic ecosystem. This project establishes a strong foundation for researchers and developers interested in PCG and its applications in creating vast and immersive environments.
Keywords: PCG; simulation; solar system; generation; planet; Marching Cubes; creature simulation; noise; Unity; ecosystem